Post-translational regulation of P2X receptor channels: modulation by phospholipids - Bernier, Louis-Philippe; Ase, Ariel; Seguela, Philippe (Frontiers in Cellular Neuroscience, 2013)
P2X receptor channels mediate fast excitatory signaling by ATP and play major roles in sensory transduction, neuro-immune communication and inflammatory response. P2X receptors constitute a gene family of calcium-permeable ATP-gated cation channels therefore the regulation of P2X signaling is critical for both membrane potential and intracellular calcium homeostasis. Phosphoinositides (PIPn) are anionic signaling phospholipids that act as functional regulators of many types of ion channels. Direct PIPn binding was demonstrated for several ligand- or voltage-gated ion channels, however no generic motif emerged to accurately predict lipid-protein binding sites. This review presents what is currently known about the modulation of the different P2X subtypes by phospholipids and about critical determinants underlying their sensitivity to PIPn levels in the plasma membrane. All functional mammalian P2X subtypes tested, with the notable exception of P2X5, have been shown to be positively modulated by PIPn, i.e. homomeric P2X1, P2X2, P2X3, P2X4, and P2X7, as well as heteromeric P2X1/5 and P2X2/3 receptors. Based on various results reported on the aforementioned subtypes including mutagenesis of the prototypical PIPn-sensitive P2X4 and PIPn-insensitive P2X5 receptor subtypes, an increasing amount of functional, biochemical and structural evidence converges on the modulatory role of a short polybasic domain located in the proximal C-terminus of P2X subunits. This linear motif, semi-conserved in the P2X family, seems necessary and sufficient for encoding direct modulation of ATP-gated channels by PIPn. Furthermore, the physiological impact of the regulation of ionotropic purinergic responses by phospholipids on pain pathways was recently revealed in the context of native crosstalks between phospholipase C-linked metabotropic receptors and P2X receptor channels in DRG sensory neurons and microglia.